A new species of Matthiola (Brassicaceae, Anchonieae) from Iran - Mahmoodi, Mohammad; Zeraatkar, Amin; Ghahremaninejad, Farrokh; Maassoumi, Ali-Asghar (Phytotaxa, 2016)
Matthiola iranica sp. nov. as a new species, is here described and illustrated from the Zanjan Province, NW of Iran. Taxonomic comments on the new species are given. Its morphological characteristics is compared with its presumed closest relative, M. farinosa and geographical distribution of both species is mapped. These two species differ by characters of leaves, inflorescences, flowers, fruits, and seeds. Matthiola iranica is endemic to the northern-west of Iran.